Bahasa Inggris - Setyono, Clarissa Angelina; Berlianto, Margaretha Pink (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This research aims to investigate the effect of utilitarian value, hedonic value, social value, and economic value on trust in product and trust in seller, the effect of trust in product and trust in seller on customer engagement and repurchase intention and the effect of customer engagement on repurchase intention toward Shopee live streaming platform in Indonesia. Methods: This research uses a quantitative approach. The sample of this research are 239 by using purposive sampling method with criteria of all customer in indonesia who have made purchase through Shopee live streaming as the population. Data analysis for this research is using SmartPLS-SEM Finding: The finding reveals that customer perceived values dimension have a partial effect on customer trust. Customer trust has significant impact in both customer engagement and repurchase intention and customer engagement have a positive effect on repurchase intention Theoretical contribution/Originality: This study contributes theoretically by examining the relationship between customer perceived value, consumer trust in customer engagement and repurchase intention. Practitioner/Policy implication: Practically, it suggests that seller’s who use Shopee live streaming platform should pay attention about products utilitarian value, social value and economic value since its effect on customer trust and also pay attention in customer trust in product and seller and customer engagement. Research limitation: The data of this research were collected only via questioner survey on online basis.